INVESTIGATION OF NURSES' COMPLIANCE WITH ISOLATıON PRECAUTIONS IN THE COVID-19 PANDEMIC - AŞKAR, Selva Ezgi; AYTEKİN KANADLI, Keriman; ÇUBUKCU, Emine; KARA SÖYLEMEZ, Gönül; SAZAK, Yasemin; ODABAŞI, Rahşan (Göbeklitepe Medical Science Journal, 2022)
In this study, it was aimed to examine the compliance of nurses with isolation precautions during the COVID-19 pandemic. A descriptive and cross-sectional study design was used. The data were collected in a university hospital between April 21 and August 1, 2020, using the "Personal Information Form" and the "Scale Compliance with Isolation Precautions" by electronic questionnaire (Google form). 109 nurses (62.4% in the 18-29 age group, 67% female, 75.2% bachelor's degree, and 37.6% of them have a professional working period of 5-9 years) participated in the study. It was determined that the total mean score of the nurses' compliance with isolation precautions was 80.31±13.14. There was no statistically significant difference between nurses' scale total score averages and age, gender, previous use of isolation methods, compliance with isolation precautions, and their characteristics for the COVID-19 pandemic (The situation of receiving training on COVID-19 before starting to work in the relevant unit, following the developments regarding the COVID-19 pandemic, and having problems in applying isolation precautions while providing care to the COVID-19 patient) (p>0.05). However, it was found that the difference between the education level and the duration of working in the profession and the total score averages on the scale was statistically significant (p<0.05). Conclusion: It was determined that the level of compliance of nurses with isolation precautions was high in the COVID-19 pandemic. However, it was seen that the characteristics of the nurses for the COVID-19 pandemic and the level of compliance with the isolation precautions were not related.